EFFECT OF CASH RECONCILIATION ON THE FINANCIAL PERFORMANCE OF COMMERCIAL BANKS IN KENYA - Onwonga, Mactosh; Achoki, Prof. George; Omboi, Dr. Bernard (International Journal of Finance, 2017)
Purpose: The main aim of the study was to examine the effect of cash reconciliation on the financial performance of commercial banks in Kenya. Methodology: The research was carried out through a descriptive survey research design. The study population was all the 43 commercial banks registered and licensed to operate in Kenya. A multi stage sampling approach was used. In the first stage, a census of all the 43 commercial banks was conducted, that is, the units of analysis were the commercial bank. In the second stage, purposive sampling was used where two respondents from every organization were taken. The study used both primary and secondary data for analysis. Primary data was collected using questionnaires while secondary data was obtained using secondary data collection template. A multiple linear regression model was used to link variables. Findings: The study findings indicated a positive correlation between cash reconciliation and financial performance of commercial banks. Cash reconciliation was positively and significantly related to both ROE and ROA. The study concluded that cash reconciliation is positively and significantly related to financial performance of commercial banks in Kenya. Unique contribution to theory, practice and policy: The study recommends that commercial banks and other financial institutions involved in handling of cash should put in place proper reconciliation practices. The commercial banks should focus on increasing the number of times books are reconciled, increase the regularity of auditing the cash books, put in place and implement a policy on cash reconciliation, training its staff on conducting cash reconciliation and segregating the duties of cash reconciliation other duties so as to evolve specialization. The study recommended further studies to establish the effect of cash handling practices on financial performance of other financial institutions other than commercial banks. This will be crucial in comparison of the results and identification of more research gaps for future studies.